2010
DOI: 10.1259/bjr/16360063
|View full text |Cite
|
Sign up to set email alerts
|

Radiology reporting: a general practitioner's perspective

Abstract: Unlike hospital-based clinicians, general practitioners (GPs) lack direct contact with radiologists, and the radiology report is usually the sole method of communication from the radiologist to the GP. It is important to gain feedback regarding what GPs perceive as a good-quality radiology report, especially in the current climate of competition for provision of radiology services. The aims of this study are to determine the level of GP satisfaction with radiology reports, their perception of optimum report co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 11 publications
5
66
1
Order By: Relevance
“…The same author conducted a survey of general practitioners and identified similar results. 10 Our study, however, demonstrated clear preference for more detailed reports in the setting of lumbar spine cross-sectional imaging, without significant preference for either prose or itemized formats, suggesting that completeness is preferred over report style.…”
Section: Formatcontrasting
confidence: 53%
“…The same author conducted a survey of general practitioners and identified similar results. 10 Our study, however, demonstrated clear preference for more detailed reports in the setting of lumbar spine cross-sectional imaging, without significant preference for either prose or itemized formats, suggesting that completeness is preferred over report style.…”
Section: Formatcontrasting
confidence: 53%
“…This study did not examine whether report format impact comprehension or speed with which the reports were read. A follow-up study [16] with general physicians from 19 different specialties confirmed the initial results.…”
Section: Introductionsupporting
confidence: 57%
“…If findings are conveyed to the referring clinicians the time and means of communication should be recorded (3,6).…”
Section: Special Article Optimizing Communication Between the Radiolomentioning
confidence: 99%
“…Specific guidelines for reporting to GPs include the following advices (3,4,6,7): platforms allowing optimal data exchange between GP and radiologists.…”
Section: The Radiology Reportmentioning
confidence: 99%